Major contribution of the 3/6/7 class of TRPC channels to myocardial ischemia/reperfusion and cellular hypoxia/reoxygenation injuries - He, Xiju (2017)
Fil: He, Xiju. Huazhong University of Science and Technology. Tongji Medical College. Department of Anatomy; China